Electrical wiring, residential / Ray C. Mullin - Mullin, Ray C. (Delmar, 1996)
Here s a comprehensive, step-by-step approach to learning all aspects of residential electrical wiring. Fully updated to reflect changes in the 1996 National Electrical Code, the 12th edition of this popular text covers every phase of house wiring, from the simplest circuit to complicated and in-depth computations to determine service-entrance, branch-circuit, and feeder sizes. Students knowledge builds with each successive unit, room by room, until every possible facet of house wiring has been covered in detail.. The new edition includes the latest wiring technologies, new coverage of fire-rated walls, lighting, HVAC equipment, as well as updated OSHA safety information. A new expanded index locates topics either by alphabetical word listing, or by 1996 NEC section number.. Loaded with examples, tables, wiring diagrams, illustrations, photographs, review questions, and a complete set of electrical plans, this unrivaled book ensures a solid understanding of residential electrical wiring.